Metabolism of novel anti-HIV agent 3-cyanomethyl-4-methyl-DCK by human liver microsomes and recombinant CYP enzymes - Zhuang Xiao-mei; Deng Jing-ting; Li Hua; Kong Wei-li; Ruan Jin-xiu; Xie Lan (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the metabolism of 3-cyanomethyl-4-methyl-DCK (CMDCK), a novel anti-HIV agent, by human liver microsomes (HLMs) and recombinant cytochrome P450 enzymes (CYPs). Methods: CMDCK was incubated with HLMs or a panel of recombinant cytochrome P450 enzymes including CYP1A2, 2B6, 2C8, 2C9, 2C19, 2D6, 3A4, and 3A5. LC-ion trap mass spectrometry was used to separate and identify CMDCK metabolites. In the experiments with recombinant cytochrome P450 enzymes, specific chemical inhibitors combined with CYP antibodies were used to identify the CYP isoforms involved in CMDCK metabolism. Results: CMDCK was rapidly and extensively metabolized by HLMs. Its intrinsic hepatic clearance estimated from the in vitro data was 19.4 mL·min−1·kg−1, which was comparable to the mean human hepatic blood flow rate (20.7 mL·min−1·kg−1). The major metabolic pathway of CMDCK was oxidation, and a total of 14 metabolites were detected. CYP3A4 and 3A5 were found to be the principal CYP enzymes responsible for CMDCK metabolism. Conclusion: CMDCK was metabolized rapidly and extensively in human hepatic microsomes to form a number of oxidative metabolites. CYP3A4 and 3A5 were the predominant enzymes responsible for the oxidation of CMDCK.